A new approach for flicker analysis using information‐theory‐based wavelet energy entropy. Issue 6 (18th July 2017) - Silsüpür, Murat; Türkay, Belgin Emre
Abstract : Flicker is one of the critical power quality disturbances seen in power distribution networks nowadays. Besides its effects on the human life, it causes malfunctioning and misoperation of sensitive electrical equipment. The measurement of the flicker level is defined in IEC 61000‐4‐15 standard by a flicker meter, which deals only with voltage signals and is not sufficient to understand the contribution of the load and background power systems separately. Therefore, in this letter we present a new approach to the evaluation of flicker characteristics in the light of multiresolution wavelet analysis and information‐theory‐based wavelet energy entropy analysis together. © 2017 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.